Association between matrix Gla protein and ulcerative colitis according to DNA microarray data. (29th October 2019) - Dong, Xu-Yang; Wu, Mei-Xu; Zhang, Hui-Min; Lyu, Hong; Qian, Jia-Ming; Yang, Hong
Abstract: Background: Matrix Gla protein (MGP) is a secreted protein contributed to the immunomodulatory functions of mesenchymal stromal cells. Microarray profiling found a significantly higher expression level of the extracellular matrix gene MGP in patients with ulcerative colitis (UC). However, little is known about the role of MGP in UC and its upstream signaling regulation. This study aimed to identify the expression of MGP in UC and its upstream regulator mechanism. Methods: Colonic mucosa biopsies were obtained from patients with UC and healthy controls. DNA microarray profiling was used to explore underlying genes correlating with UC development. Mice were fed with water containing different concentrations of dextran sodium sulfate (DSS) to induce an experimental colitis model. Colonic tissues were collected and evaluated using immunohistochemistry, immunoblot, real-time polymerase chain reaction, and chromatin immunoprecipitation assay. Bioinformatics analysis was performed to identify candidate MGP gene-promoter sequence and transcription-initiation sites. Luciferase-reporter gene assay was conducted to examine the potential transcription factor of MGP gene expression. Results: The expression of MGP was significantly increased in colonic tissues from UC patients and DSS-induced colitis models, and was positively correlated with disease severity. Bioinformatics analysis showed a conserved binding site for Egr-1 in the upstream region of human MGP gene. The significantly higher level of Egr-1 gene expression was found in UC patients than in healthy controls. The activity of luciferase was significantly enhanced in the Egr-1 expression plasmid co-transfected group than in the control group and was further inhibited when co-transfected with the Egr-1 binding-site mutated MGP promoter. Conclusions: Up-regulated expression of MGP was found in UC patients and DSS-induced colitis. The expression of MGP can be regulated by Egr-1.